Super-hydrophobic composite coating with multi-layer self-similar anchoring structure and preparation method of super-hydrophobic composite coating
By adopting a multi-layer self-similar anchor structure design in the superhydrophobic coating, the problems of rapid disappearance of superhydrophobic properties and poor mechanical properties of the existing superhydrophobic coating are solved, and the high wear resistance and impact resistance of the coating are achieved ensures the continuous effectiveness of hydrophobic properties.
Patent Information
- Application Number
- CN202411496534.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing superhydrophobic coatings have problems such as fast disappearance of superhydrophobic properties, poor mechanical properties, poor impact resistance, and insufficient adhesion between the coating and the substrate.
Using a superhydrophobic composite coating with multiple layers of self-similar anchoring structure, including a superhydrophobic bottom layer and a superhydrophobic surface layer with self-similar anchoring structure, prepared by layering coating, micro-nano pores are formed between the bottom layer and the surface layer. Structure, enhances the mechanical durability and impact resistance of the coating.
It significantly improves the wear resistance and impact resistance of superhydrophobic coatings, extends the service life of the coating, ensures that the hydrophobic performance of the supercomposite coatings is continuously effective, and the static water contact angle reaches 163°±0.8°, and in various Good performance was shown in the wear and corrosion test.
Smart Images

Figure CN119500531A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrophobic materials, and in particular to a super-hydrophobic composite coating with a multi-layer self-similar anchoring structure and a preparation method thereof. Background Art
[0002] Generally, the surface with a water contact angle greater than 150 ° and a water sliding angle less than 10 ° is defined as a super-hydrophobic surface, which is inspired by natural lotus leaves. Although the super-hydrophobic surface has excellent hydrophobicity, self-cleaning, anti-fouling and anti-icing properties, the application of the current super-hydrophobic coating is limited due to poor durability, because the mechanical wear resistance of the coating is poor, the low surface energy material on the surface cannot be replenished after consumption, and the damaged rear surface super-hydrophobic performance is easily lost, and the micro-nano rough structure on the surface is easily destroyed, so that the super-hydrophobic ability on the surface is sharply reduced. At the same time, the manufacturing method is usually complicated, expensive and time-consuming. Existing patent CN118307213A discloses a super-hydrophobic coating glass and a preparation method thereof, including a glass substrate and a hydrophobic coating attached to a glass substrate, and the hydrophobic coating is formed by applying a configured coating composition to a glass surface and curing, and the components of the coating composition include silicon dioxide particles, titanium dioxide, polyvinyl alcohol, deionized water, polyethylene glycol, fluorinated silane and benzyltrimethoxysilane. The prepared glass has the advantages of good hydrophobicity and high light transmittance. However, the mechanical properties of the prepared coating are poor, and its super hydrophobic performance deteriorates due to mechanical external force damage. Patent CN118162346A discloses an aluminum alloy super hydrophobic corrosion-resistant coating and its preparation method and application, comprising the following steps: placing a pretreated aluminum alloy substrate in a corrosion-resistant coating liquid for dip coating, then curing, and forming a corrosion-resistant coating on the surface of the aluminum alloy; spraying a leveling transition coating liquid on the surface of the aluminum alloy containing the corrosion-resistant layer, then applying an alternating rotating magnetic field to the aluminum alloy accompanied by mechanical vibration, and then curing to form a leveling transition layer on the corrosion-resistant coating; spraying a super hydrophobic coating liquid on the surface of the aluminum alloy containing the leveling transition layer, then curing, and forming a super hydrophobic coating on the leveling transition layer. The prepared aluminum alloy substrate has a good corrosion protection effect for a long time. However, its preparation method is cumbersome, the preparation process is complicated, and the application field is limited. Patent CN106119842A discloses a double-layer super hydrophobic material and its preparation method. The alloy substrate was immersed in a mixed solution of equal volumes of stearic acid ethanol solution and nickel sulfate aqueous solution, and hydrothermal treatment was performed at 140°C for 7 hours. After cooling, the substrate was taken out and dried, and then immersed in a mixed solution of equal volumes of stearic acid ethanol solution and cobalt sulfate aqueous solution in a certain proportion, and hydrothermal treatment was performed at 130°C for 8 hours; after cooling, the substrate was taken out and dried to obtain a double-layer super-hydrophobic material. The prepared super-hydrophobic material gives the alloy long-term corrosion resistance and anti-fouling properties. However, the interlayer bonding strength of the upper and lower layers is not good, and the overall mechanical stability is not good.
[0003] Therefore, it is necessary to solve the technical problems of existing super-hydrophobic coatings, such as the rapid disappearance of super-hydrophobic properties, poor mechanical properties, poor impact resistance, and insufficient adhesion between the coating and the substrate. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a super-hydrophobic composite coating with a multi-layer self-similar anchoring structure and a preparation method thereof, so as to solve the technical problems of existing super-hydrophobic coatings such as rapid disappearance of super-hydrophobic properties, poor mechanical properties, poor impact resistance, and insufficient adhesion between the coating and the substrate.
[0005] The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure of the present invention comprises a super-hydrophobic bottom layer and a super-hydrophobic surface layer with a self-similar anchoring structure, wherein the super-hydrophobic bottom layer and the super-hydrophobic surface layer interact with each other to form a micro-nano porous structure for bonding and anchoring the upper and lower layers, and the surface of the coating has a multi-scale micro-nano composite structure, and when the super-hydrophobic surface layer is worn, the super-hydrophobic bottom layer performs a hydrophobic function;
[0006] Further, the raw materials of the super hydrophobic bottom layer include solvents, high-strength adhesive materials, toughening materials, highly inert nanoparticles, film-forming materials, plasticizing materials, filler granular rough materials and curing materials; the raw materials of the super hydrophobic surface layer include solvents, highly inert nanoparticles, low surface energy materials and silicone elastomers;
[0007] Further, by weight, the raw material of the super-hydrophobic bottom layer includes 50-70 parts of solvent, 10-30 parts of high-strength adhesive material, 8-25 parts of toughening material, 1-3 parts of highly inert nanoparticles, 5-20 parts of film-forming material, 0.5-2 parts of plasticizer, 1-3 parts of filler, 8-12 parts of granular rough material, and 0.2-0.6 parts of curing material; the raw material of the super-hydrophobic surface layer includes 25-40 parts of solvent, 1-3 parts of highly inert nanoparticles, 1-3 parts of low surface energy material, and 0.6-1.5 parts of functional additive material;
[0008] Furthermore, the solvent is at least one of anhydrous ethanol, acetone, toluene, and tetrahydrofuran; the high-strength adhesive material is epoxy resin; the toughening material is at least one of polyester resin, acrylic resin, polyurethane resin, and alicyclic polyamine; the highly inert nanoparticles are at least one of R106, R202, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720 in hydrophobic gas-phase nano-SiO2;
[0009] Furthermore, the film-forming material is polysiloxane; the plasticizing material is at least one of polymethyl methacrylate, phenolic resin, and polypropylene; the filler is at least one of quartz powder, talcum powder, aluminum powder, or titanium dioxide; the granular rough material is at least one of quartz sand, river sand, and machine-made sand; the curing material is at least one of linear aliphatic polyamine, polyamide, and polythiol;
[0010] Furthermore, the low surface energy substance is polydimethylsiloxane; and the functional additive material is at least one of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane.
[0011] The present invention also discloses a method for preparing a super-hydrophobic composite coating having a multi-layer self-similar anchoring structure, which adopts a layered coating method, firstly coating a super-hydrophobic bottom layer solution on the surface of a substrate and curing the substrate, and then coating a super-hydrophobic surface layer solution;
[0012] Further, the preparation of the super hydrophobic bottom layer solution comprises the following steps:
[0013] The high-strength adhesive material, the film-forming material and the plasticizing material are dissolved in a solvent, stirred and ultrasonically dispersed to obtain a solution A; the highly inert nanoparticles, the toughening material and the filler are mixed and dissolved in a solvent, stirred and ultrasonically dispersed to obtain a solution B; the solution A, the solution B, the curing material and the granular rough material are mixed;
[0014] Furthermore, the method for preparing the super-hydrophobic surface layer solution comprises the following steps:
[0015] Highly inert nanoparticles are dispersed in anhydrous ethanol to obtain a gas-phase nano-silica suspension, and then a low surface energy substance is added and stirred, and finally a functional additive material is added and stirred and ultrasonically dispersed.
[0016] The invention has the beneficial effects as follows: the preparation method of the super-hydrophobic composite coating with multi-layer self-similar anchoring structure of the invention, the prepared coating has a multi-layer micro-nano anchoring wear-resistant structure, and each layer has a similar structure, the interlayer interaction bonding anchoring is integrated, the prepared double-layer coating has excellent super-hydrophobic performance and high mechanical durability, this multi-layer self-similar structure can effectively improve the wear resistance and impact resistance of the surface of the super-hydrophobic coating, the bottom layer can withstand the main force when the surface layer is mechanically damaged, reduce the degree of wear and tear on the coating surface, even if the coating surface is worn, the newly exposed coating surface can also show good hydrophobic performance, ensuring that the hydrophobic performance of the super-composite coating is continuously effective. The prepared coating static water contact angle reaches 163 ° ± 0.8 °, and the rolling angle is 3 ° ± 0.8 °. The coating still maintains super-hydrophobicity after 150 cycles of sandpaper friction under 300g pressure, and the contact angle decreases by only 6.1%. After 16 hours of water drop penetration test and 12 hours of water flow impact test, the contact angle of the coating remained above 153° and 151°. After the coating was immersed in acidic, alkaline and salt solutions for 8 hours respectively, the contact angle of the coating was still above 150°, and the rolling angle remained below 10°, still maintaining super hydrophobicity, showing good corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0018] Figure 1 The SEM image of the surface of the durable self-similar superhydrophobic composite coating;
[0019] Figure 2 FTIR spectra of different coating samples: a: super hydrophobic coating b: hydrophobic bonding coating;
[0020] Figure 3 is the wettability of the coating after mechanical wear;
[0021] Figure 4 The wettability of the coating after tape stripping;
[0022] Figure 5 is the wettability of the coating after water droplet impact;
[0023] Figure 6 It is the wettability of the coating after water impact. DETAILED DESCRIPTION
[0024] The super-hydrophobic composite coating with multi-layer self-similar anchoring structure of the present embodiment, including a super-hydrophobic bottom layer and a super-hydrophobic surface layer with a self-similar anchoring structure, the super-hydrophobic bottom layer and the super-hydrophobic surface layer interact to form a micro-nano porous structure for bonding and anchoring the upper and lower layers, and the coating surface has a multi-scale micro-nano composite structure. When the super-hydrophobic surface layer is worn, the super-hydrophobic bottom layer exercises a hydrophobic function; preferably, a double-layer structure combined with the bottom layer and the surface layer is used. The bottom layer is not only closely combined with the substrate, but also effectively interacts with the super-hydrophobic coating of the surface layer, which promotes the formation and stability of the micro-nano structure inside the coating. The composite coating can still maintain the integrity of its structure and performance when subjected to external wear or impact. The coating surface has a multi-scale micro-nano composite structure, which not only has the necessary roughness required for the super-hydrophobic coating, but also significantly increases the air interception capacity of the coating surface, forming an effective air isolation pad, thereby greatly improving the super-hydrophobic performance of the coating. More importantly, the multi-scale micro-nano structure can show its advantages step by step during the wear process. Even if the top layer is damaged, the bottom layer of the strong and durable hydrophobic film with a self-similar anchoring structure can still maintain complete hydrophobicity, ensuring that the hydrophobic performance of the supercomposite coating remains effective. This self-similar structural design greatly extends the service life of the durable superhydrophobic composite coating.
[0025] In the present embodiment, the super-hydrophobic bottom layer raw material includes solvent, high-strength adhesive material, toughening material, high inert nanoparticles, film-forming material, plasticizing material, filler granular rough material and curing material; the super-hydrophobic surface layer raw material includes solvent, high inert nanoparticles, low surface energy material, silicone elastomer; the epoxy resin in the bottom layer has excellent adhesion and chemical stability, which can make the bottom coating firmly attached to the substrate surface by strong adhesion, and firmly combined with high inert nanoparticle particles. Its cross-linked structure makes the coating form a solid matrix after curing, which helps to improve the stability of the overall coating. The polysiloxane in the bottom layer provides excellent weather resistance and water resistance, while the plasticizer enhances the heat resistance and mechanical strength of the coating. The two work together to form a powerful protective layer in the bottom coating. The filler in the bottom layer fills the pores of the cross-linked structure to a certain extent, provides certain wear resistance and rheological properties, can improve the construction performance of the coating, and make it easier to apply and dry. At the same time, the filler and the granular rough material provide additional mechanical strength together, which enhances the structural strength of the coating. The toughening material in the bottom layer improves the mechanical strength and toughness of the coating, enhances its wear resistance and impact resistance, and thus extends the service life of the coating. By improving the structure and physical properties of the coating, the toughening material effectively prevents the coating from cracking, peeling and damage in daily use, ensuring the long-term stability of the coating. The granular rough material in the bottom layer has excellent wear resistance and hardness, and can improve the impact resistance and scratch resistance of the coating. Its rough structure together with nano-SiO2 provides additional mechanical strength, enhancing the strength and durability of the coating.
[0026] The low surface energy material in the surface layer is the main source of low surface energy in the super hydrophobic coating, which can effectively prevent the adhesion of water and dirt. The composite of polydimethylsiloxane and nano-SiO2 makes the coating extremely hydrophobic. It not only enhances the hardness and wear resistance of the surface, but also makes the coating have excellent self-cleaning ability.
[0027] A preferred embodiment is that, by weight, the raw materials for the super-hydrophobic base layer include 50-70 parts of solvent, 10-30 parts of high-strength adhesive material, 8-25 parts of toughening material, 1-3 parts of highly inert nanoparticles, 5-20 parts of film-forming material, 0.5-2 parts of plasticizer, 1-3 parts of filler, 8-12 parts of granular rough material, and 0.2-0.6 parts of curing material; the raw materials for the super-hydrophobic surface layer include 25-40 parts of solvent, 1-3 parts of highly inert nanoparticles, 1-3 parts of low surface energy material, and 0.6-1.5 parts of functional additive material.
[0028] In this embodiment, the solvent is at least one of anhydrous ethanol, acetone, toluene, and tetrahydrofuran; the high-strength adhesive material is epoxy resin; the toughening material is at least one of polyester resin, acrylic resin, polyurethane resin, and alicyclic polyamine; the highly inert nanoparticles are at least one of R106, R202, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720 in hydrophobic gas-phase nano-SiO2; the film-forming material is polysiloxane; The plastic material is at least one of polymethyl methacrylate, phenolic resin, and polypropylene; the filler is at least one of quartz powder, talcum powder, aluminum powder, or titanium dioxide; the granular rough material is at least one of quartz sand, river sand, and machine-made sand; the curing material is at least one of linear aliphatic polyamines, polyamides, and polythiol; the low surface energy substance is polydimethylsiloxane; the functional additive material is at least one of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane. The polydimethylsiloxane in the surface layer is an excellent low surface energy material and is the main source of low surface energy in the super-hydrophobic coating. It can effectively prevent the attachment of moisture and dirt. The polydimethylsiloxane and nano-SiO2 composite make the coating extremely hydrophobic. Not only does it enhance the hardness and wear resistance of the surface, but it also makes the coating have excellent self-cleaning ability. The functional additive materials in the surface layer are highly reactive and can form a cross-linked network with other silicon-based materials to further enhance the surface roughness and hydrophobicity of the coating. The introduction of modified materials combined with nano-SiO2 and granular rough materials to provide roughness, polydimethylsiloxane to provide low surface energy, together provide extremely high hydrophobicity, reduce the adhesion of dirt and dust, and greatly enhance the self-cleaning function. The hydrophobic gas-phase nano-SiO2 used in the bottom and top coatings has an extremely small particle size and a high specific surface area, which can significantly improve the hardness, wear resistance and surface smoothness of the coating. In addition, nano-SiO2 can effectively improve the UV resistance of the coating and extend its service life. The nano-SiO2, granular rough structure and filler of the bottom coating provide excellent wear resistance, while the granular rough material further enhances the wear resistance of the coating. This multi-level wear-resistant design performs significantly in high-friction and high-impact environments. The sand particles in the bottom layer can replace most of the surface super-hydrophobic coating when it is worn, and can be used to protect the super-hydrophobicity of the surface coating, which can effectively improve the mechanical properties and impact resistance of the coating, and achieve excellent durability in line with the super-hydrophobic coating. The application of composite resins and nanomaterials in the bottom and surface coatings improves the chemical resistance of the coating, enabling it to resist the erosion of various chemicals and is suitable for harsh environments such as the chemical industry. The combination of multiple resins and nanomaterials improves the weather resistance of the coating, enabling it to resist the influence of ultraviolet rays, moisture and temperature changes, and maintains the stability of the coating's performance.The double-layer multi-level super-hydrophobic coating can be applied to a variety of substrate surfaces, including rough surfaces such as concrete and mortar, and smooth surfaces such as metal.
[0029] The preparation method of the super-hydrophobic composite coating with multi-layer self-similar anchoring structure of the present embodiment example, adopts the mode of layered brushing, first brushes the super-hydrophobic bottom solution on the substrate surface and solidifies it, and then brushes the super-hydrophobic surface layer solution; The preparation of the super-hydrophobic bottom solution comprises the following steps: high-strength adhesive material, film-forming material and plasticizing material are dissolved in solvent and stirred and ultrasonically dispersed to obtain solution A; High inert nanoparticles, toughening materials, and fillers are mixed and dissolved in solvent and stirred and ultrasonically dispersed to obtain solution B; Solution A, solution B, solidified materials and granular rough materials are mixed; The preparation method of the super-hydrophobic surface layer solution comprises the following steps: high inert nanoparticles are dispersed in anhydrous ethanol to obtain a gas-phase nano-silicon dioxide suspension, then low surface energy materials are added to stir, and finally functional additive materials are added to stir and ultrasonically disperse. The hydrophobic film prepared by the present invention evenly and firmly anchors granular rough materials on the substrate surface, constructs a tight and tough wear-resistant bottom layer. The granular rough material, with its high hardness, height difference formed on the surface of the substrate and uniform distribution, significantly improves the impact strength and wear resistance of the coating, thereby effectively extending the service life of the coating. The excellent adhesion strength exhibited by the hydrophobic film is mainly attributed to the synergistic effect of the epoxy resin and the toughening material after curing. In addition, the addition of the film-forming material further enhances the tear resistance and wear resistance of the composite coating. The bottom layer is not only tightly combined with the substrate, but also effectively interacts with the super-hydrophobic coating of the surface layer, promoting the formation and stability of the micro-nano structure inside the coating. The composite coating can still maintain the integrity of its structure and performance when subjected to external wear or impact. The coating surface is jointly constructed by micron-sized granular rough materials and nano-sized SiO2 particles to form a multi-scale micro-nano composite structure, which not only has the necessary roughness required for the super-hydrophobic coating, but also significantly increases the air interception capacity of the coating surface, forming an effective air isolation pad, thereby greatly improving the super-hydrophobic performance of the coating. More importantly, the multi-scale micro-nano structure can show its advantages step by step during the wear process. Even if the top layer structure is damaged, the bottom layer with a strong and durable hydrophobic film with a self-similar anchoring structure can still maintain complete hydrophobicity, ensuring that the hydrophobic performance of the supercomposite coating remains effective. This self-similar structural design greatly extends the service life of the durable superhydrophobic composite coating, demonstrating its great potential and advantages in practical applications.
[0030] The present invention introduces a highly active organosilicon monomer as a functional additive material on the basis of combining traditional polydimethylsiloxane with nano-SiO2 to form a super-hydrophobic coating. After the highly active organosilicon monomer is compounded with polymer materials such as polydimethylsiloxane, a large number of micro-nano epitaxial structures are successfully constructed on the coating surface, which significantly reduces the surface energy of the coating, thereby optimizing the surface wettability of the composite coating and increasing the contact angle from 156° to 163°. Since the organosilicon monomer can react chemically with other silicon-based materials such as dimethylsiloxane to form a stable cross-linked network, it not only enhances the bonding strength inside the super-hydrophobic surface layer, but also promotes the close combination between the surface layer and the bottom layer. When impacted or worn, this strong bonding force can effectively prevent the coating from being delaminated or peeled off, thereby maintaining the integrity and super-hydrophobic performance of the composite coating. By forming a cross-linked network, the organosilicon monomer gives the coating a certain elasticity and flexibility, so that it can absorb and disperse the impact energy by tiny deformation when impacted, effectively preventing the coating from breaking or causing serious damage. In addition, the cross-linking effect of the organosilicon monomer significantly enhances the stability of the micro-nano structure on the coating surface. When impacted or worn, the cross-linked network can maintain the integrity and order of the micro-nano structure, preventing the micro-nano structure from being destroyed or reorganized. It is worth mentioning that the silicone monomer also exhibits excellent chemical stability and can maintain the performance of the coating under a variety of environmental conditions. When corroded by chemical substances such as acids and alkalis, the silicone monomer can work synergistically with other silicon-based materials to resist chemical attacks and prevent the surface structure of the coating from being destroyed or the performance from being degraded, thereby further improving the durability and practicality of the composite coating.
[0031] The present invention is a preparation method with low cost and simple preparation process, and has stable superhydrophobic performance, excellent adhesion and good durability. In addition, the coating also has excellent self-cleaning performance, and there is no need for cumbersome pretreatment steps such as etching or modification of the substrate surface. The coating can be applied to a variety of substrate surfaces, including smooth surfaces and rough surfaces. Smooth surfaces include glass and metal surfaces, such as steel, aluminum, copper, etc.; rough surfaces include wood, concrete, mortar, etc.; it can be applied to the shell or interior decoration of vehicles such as automobiles, ships, and airplanes, and has a wide range of applications.
[0032] Embodiment 1
[0033] The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure of this embodiment includes a base coating and a surface coating, wherein the base raw materials include, by weight, 50 parts of solvent, 10 parts of high-strength adhesion material, 8 parts of toughening material, 1 part of highly inert nanoparticles, 5 parts of film-forming material, 0.5 parts of plasticizer, 1 part of filler, 8 parts of granular rough material, and 0.2 parts of curing material; the surface raw materials include, by weight, 25 parts of solvent, 1 part of highly inert nanoparticles, 1 part of low surface energy material, and 0.6 parts of functional additive material.
[0034] In this embodiment, the solvent is anhydrous ethanol, and the anhydrous ethanol can be replaced by one of acetone, toluene, and tetrahydrofuran, or replaced by a mixture of anhydrous ethanol and acetone, toluene, and tetrahydrofuran, all of which can achieve the purpose of the present invention; the high-strength adhesive material is epoxy resin; the toughening material is polyester resin, and the polyester resin can be replaced by one of acrylic resin, polyurethane resin, and alicyclic polyamine, or replaced by a mixture of polyester resin and acrylic resin, polyurethane resin, and alicyclic polyamine, all of which can achieve the purpose of the present invention; the highly inert nanoparticles The particles are R106 in the hydrophobic gas-phase nano-SiO2. R106 can be replaced by one of R202, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, or by a mixture of R106 and R202, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, all of which can achieve the purpose of the present invention.
[0035] In this embodiment, the film-forming material is polysiloxane; the plasticizer is polymethyl methacrylate, and the purpose of the present invention can be achieved by replacing polymethyl methacrylate with one of phenolic resin and polypropylene, or by replacing it with a mixture of polymethyl methacrylate, phenolic resin and polypropylene; the filler is quartz powder, and the purpose of the present invention can be achieved by replacing quartz powder with one of talcum powder, aluminum powder or titanium dioxide, or by replacing it with a mixture of quartz powder and talcum powder, aluminum powder and titanium dioxide; the granular rough material is quartz sand, and the purpose of the present invention can be achieved by replacing quartz sand with one of river sand and machine-made sand, or by replacing it with a mixture of quartz sand and river sand or machine-made sand; the curing material is a straight-chain aliphatic polyamine, and the purpose of the present invention can be achieved by replacing the straight-chain aliphatic polyamine with one of polyamide and polythiol, or by replacing it with a mixture of straight-chain aliphatic polyamine, polyamide and polythiol.
[0036] In this embodiment, the low surface energy substance is polydimethylsiloxane; the functional additive material is octamethylcyclotetrasiloxane, and the purpose of the present invention can be achieved by replacing octamethylcyclotetrasiloxane with one of tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane, or replacing it with a mixture of octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane.
[0037] The preparation method of the bottom layer comprises the following steps: firstly, epoxy resin, polysiloxane and plasticizer are dissolved in an ethanol solution, magnetically stirred at a rotation speed of 2000 rpm for 3 hours, and then ultrasonically dispersed for 30 minutes to obtain solution A; hydrophobic gas-phase nano-SiO2, toughening material and filler are mixed and dissolved in a second ethanol solution, magnetically stirred at a rotation speed of 2000 rpm for 3 hours, and then ultrasonically dispersed for 30 minutes to obtain solution B; finally, the bottom layer solution is obtained by mixing solutions A, B, curing material and granular rough material and magnetically stirring at a rotation speed of 2000 rpm for 0.5 seconds.
[0038] The preparation method of the surface layer includes the following steps: firstly, dispersing hydrophobic gas-phase nano-SiO2 in anhydrous ethanol to obtain a gas-phase nano-silica suspension; then adding polydimethylsiloxane to the gas-phase nano-silica suspension, and magnetically stirring at 500rpm for 4 hours; then adding functional additives and magnetically stirring at a speed of 2000rpm for 3 hours, and ultrasonically dispersing for 2 hours to obtain a surface layer solution.
[0039] The coating formed by compounding the bottom layer solution and the surface layer solution is simply brushed to prepare a double-layer self-similar super-hydrophobic composite coating on the substrate surface. After the bottom layer of the coating is coated on the surface of the substrate, it is placed at room temperature for 24 hours until the solvent evaporates and the coating solidifies. The surface layer and the bottom layer are compositely inlaid and coated, placed at 60° C. to dry for 50 minutes, and then cured for 12 hours under natural room temperature conditions.
[0040] Embodiment 2
[0041] The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure of this embodiment includes a base coating and a surface coating, wherein the base raw materials include, by weight, 70 parts of solvent, 30 parts of high-strength adhesion material, 25 parts of toughening material, 3 parts of highly inert nanoparticles, 20 parts of film-forming material, 2 parts of plasticizer, 3 parts of filler, 12 parts of granular rough material, and 0.2 parts of curing material; the surface raw materials include, by weight, 40 parts of solvent, 3 parts of highly inert nanoparticles, 3 parts of low surface energy material, and 1.5 parts of functional additive material.
[0042] In this embodiment, the solvent is acetone, and the purpose of the present invention can be achieved by replacing acetone with one of anhydrous ethanol, toluene, and tetrahydrofuran, or by replacing acetone with a mixture of acetone and anhydrous ethanol, toluene, and tetrahydrofuran; the high-strength adhesive material is epoxy resin; the toughening material is acrylic resin, and the purpose of the present invention can be achieved by replacing acrylic resin with one of polyester resin, polyurethane resin, and alicyclic polyamine, or by replacing acrylic resin with a mixture of polyester resin, polyurethane resin, and alicyclic polyamine; the highly inert nanoparticles For R202 in the hydrophobic gas-phase nano-SiO2, R202 can be replaced by one of R106, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, or by a mixture of R202 and R106, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, all of which can achieve the purpose of the present invention.
[0043] In this embodiment, the film-forming material is polysiloxane; the plasticizer is phenolic resin, and the purpose of the present invention can be achieved by replacing the phenolic resin with one of polymethyl methacrylate and polypropylene, or by replacing it with a mixture of phenolic resin, polymethyl methacrylate and polypropylene; the filler is talcum powder, and the purpose of the present invention can be achieved by replacing the talcum powder with one of quartz powder, aluminum powder or titanium dioxide, or by replacing it with a mixture of talcum powder and quartz powder, aluminum powder and titanium dioxide; the granular rough material is river sand, and the purpose of the present invention can be achieved by replacing the river sand with one of quartz sand and machine-made sand, or by replacing it with a mixture of river sand, quartz sand and machine-made sand; the curing material is polyamide, and the purpose of the present invention can be achieved by replacing polyamide with one of linear aliphatic polyamine and polythiol, or by replacing it with a mixture of polyamide and linear aliphatic polyamine and polythiol.
[0044] In this embodiment, the low surface energy substance is polydimethylsiloxane; the functional additive material is tetramethyltetravinylcyclotetrasiloxane, and the purpose of the present invention can be achieved by replacing tetramethyltetravinylcyclotetrasiloxane with one of octamethylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane, or replacing it with a mixture of tetramethyltetravinylcyclotetrasiloxane and octamethylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane.
[0045] The preparation method of the bottom layer comprises the following steps: firstly, epoxy resin, polysiloxane and plasticizer are dissolved in an ethanol solution, magnetically stirred at a rotation speed of 500 rpm for 5 hours, and then ultrasonically dispersed for 30 minutes to 60 minutes to obtain solution A; hydrophobic gas-phase nano-SiO2, toughening material and filler are mixed and dissolved in a second ethanol solution, magnetically stirred at a rotation speed of 500 rpm for 5 hours, and then ultrasonically dispersed for 60 minutes to obtain solution B; finally, the bottom layer solution is obtained by mixing solutions A, B, curing material and granular rough material and magnetically stirring at a rotation speed of 500 rpm for 2 hours.
[0046] The preparation method of the surface layer includes the following steps: firstly, dispersing hydrophobic gas-phase nano-SiO2 in anhydrous ethanol to obtain a gas-phase nano-silica suspension; then adding polydimethylsiloxane to the gas-phase nano-silica suspension, and magnetically stirring at 2000rpm for 3 hours; then adding functional additives, magnetically stirring at a speed of 500rpm for 5 hours, and ultrasonically dispersing for 4 hours to obtain a surface layer solution.
[0047] In this example, the coating after the bottom layer solution and the surface layer solution are compounded is prepared by a simple brushing method to realize the preparation of a double-layer multi-level super hydrophobic coating on the substrate surface. After the coating bottom layer is coated on the substrate surface, it is placed at room temperature for 36 hours until the solvent evaporates and the coating solidifies. The surface layer and the bottom layer are compositely inlaid and coated, placed at 60°C and dried for 60 minutes, and then cured at natural room temperature for 24 hours.
[0048] Embodiment 3
[0049] The coating consists of two parts, including a base coating and a surface coating, wherein the base raw materials include, by weight, 60 parts of solvent, 20 parts of high-strength adhesion material, 17 parts of toughening material, 2 parts of high-inert nanoparticles, 10 parts of film-forming material, 1.5 parts of plasticizer, 2 parts of filler, 10 parts of granular rough material, and 0.3 parts of curing material; the surface raw materials include, by weight, 35 parts of solvent, 2 parts of high-inert nanoparticles, 2 parts of low surface energy material, and 1 part of functional additive material.
[0050] In this embodiment, the solvent is toluene, and the purpose of the present invention can be achieved by replacing toluene with one of acetone, anhydrous ethanol, and tetrahydrofuran, or by replacing toluene with a mixture of acetone, anhydrous ethanol, and tetrahydrofuran; the high-strength adhesive material is epoxy resin; the toughening material is polyurethane resin, and the purpose of the present invention can be achieved by replacing polyurethane resin with one of acrylic resin, polyester resin, and alicyclic polyamine, or by replacing polyurethane resin with a mixture of acrylic resin, polyester resin, and alicyclic polyamine; the highly inert nanoparticles For R812 in the hydrophobic gas-phase nano-SiO2, R812 can be replaced by one of R202, R106, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, or by a mixture of R812 and R202, R106, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, all of which can achieve the purpose of the present invention.
[0051] In this embodiment, the film-forming material is polysiloxane; the plasticizing material is polypropylene, and the purpose of the present invention can be achieved by replacing polypropylene with one of phenolic resin and polymethyl methacrylate, or replacing it with a mixture of polypropylene and phenolic resin or polymethyl methacrylate; the filler is aluminum powder, and the purpose of the present invention can be achieved by replacing aluminum powder with one of talcum powder, quartz powder or titanium dioxide, or replacing it with a mixture of aluminum powder and talcum powder, quartz powder or titanium dioxide. The granular rough material is quartz sand, and the purpose of the present invention can be achieved by replacing quartz sand with one of river sand and machine-made sand, or replacing it with a mixture of quartz powder and quartz sand and river sand or machine-made sand; the curing material is polythiol, and the purpose of the present invention can be achieved by replacing polythiol with one of polyamide and linear aliphatic polyamine, or replacing it with a mixture of polythiol and polyamide or linear aliphatic polyamine.
[0052] In this embodiment, the low surface energy substance is polydimethylsiloxane; the functional additive material is methylvinylcyclotrisiloxane, and the purpose of the present invention can be achieved by replacing methylvinylcyclotrisiloxane with one of tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, octamethylcyclotetrasiloxane, and methylvinylcyclopentasiloxane, or by replacing it with a mixture of tetravinylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane, octamethylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane.
[0053] The preparation method of the bottom layer comprises the following steps: firstly, epoxy resin, polysiloxane and plasticizer are dissolved in an ethanol solution, magnetically stirred at a rotation speed of 1000 rpm for 4 hours, and then ultrasonically dispersed for 40 minutes to obtain solution A; hydrophobic gas-phase nano-SiO2, toughening material and filler are mixed and dissolved in a second ethanol solution, magnetically stirred at a rotation speed of 1000 rpm for 4 hours, and then ultrasonically dispersed for 40 minutes to obtain solution B; finally, the bottom layer solution is obtained by mixing solutions A, B, curing material and granular rough material and magnetically stirring at a rotation speed of 1000 rpm for 1 hour.
[0054] The preparation method of the surface layer includes the following steps: firstly, dispersing hydrophobic gas-phase nano-SiO2 in anhydrous ethanol to obtain a gas-phase nano-silica suspension; then adding polydimethylsiloxane to the gas-phase nano-silica suspension, and magnetically stirring at 1000 rpm for 3.5 hours; then adding functional additives, magnetically stirring at a speed of 1000 rpm for 4 hours, and ultrasonically dispersing for 3 hours to obtain a surface layer solution.
[0055] In this example, the coating formed by compounding the bottom layer solution and the surface layer solution is simply brushed to prepare a double-layer multi-level super-hydrophobic coating on the substrate surface. After the bottom layer of the coating is coated on the surface of the substrate, it is placed at room temperature for 30 hours until the solvent evaporates and the coating solidifies. The surface layer and the bottom layer are compositely inlaid and coated, placed at 60°C for 55 minutes, and then cured at natural room temperature for 18 hours.
[0056] Embodiment 4
[0057] The coating consists of two parts, including a base coating and a surface coating. The base coating raw materials include, by weight, 50 parts of solvent, 10 parts of high-strength adhesion material, 8 parts of toughening material, 1 part of highly inert nanoparticles, 5 parts of film-forming material, 0.5 parts of plasticizer, 1 part of filler, 8 parts of granular rough material, and 0.45 parts of curing material; the surface coating raw materials include, by weight, 40 parts of solvent, 3 parts of highly inert nanoparticles, 3 parts of low surface energy material, and 1.5 parts of functional additive material.
[0058] In this embodiment, the solvent is tetrahydrofuran, and the purpose of the present invention can be achieved by replacing tetrahydrofuran with one of acetone, toluene, and anhydrous ethanol, or by replacing it with a mixture of tetrahydrofuran and acetone, toluene, and anhydrous ethanol; the high-strength adhesive material is epoxy resin; the toughening material is alicyclic polyamine, and the purpose of the present invention can be achieved by replacing the alicyclic polyamine with one of acrylic resin, polyurethane resin, and polyester resin, or by replacing it with a mixture of alicyclic polyamine and acrylic resin, polyurethane resin, and polyester resin; the highly inert nanoparticles The particles are R812S in hydrophobic gas-phase nano-SiO2. R812S can be replaced by one of R202, R812, R106, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, or by a mixture of R812S and R202, R812, R106, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720, all of which can achieve the purpose of the present invention.
[0059] In this embodiment, the film-forming material is polysiloxane; the plasticizer is phenolic resin, and the purpose of the present invention can be achieved by replacing the phenolic resin with one of polymethyl methacrylate and polypropylene, or by replacing it with a mixture of phenolic resin, polymethyl methacrylate and polypropylene; the filler is titanium dioxide, and the purpose of the present invention can be achieved by replacing titanium dioxide with one of talcum powder, aluminum powder or quartz powder, or by replacing it with a mixture of quartz sand and talcum powder, aluminum powder and titanium dioxide; the granular rough material is quartz sand, and the purpose of the present invention can be achieved by replacing quartz sand with one of river sand and machine-made sand, or by replacing it with a mixture of quartz powder and quartz sand, river sand and machine-made sand; the curing material is a straight-chain aliphatic polyamine, and the purpose of the present invention can be achieved by replacing the straight-chain aliphatic polyamine with one of polyamide and polythiol, or by replacing it with a mixture of straight-chain aliphatic polyamine, polyamide and polythiol.
[0060] In this embodiment, the low surface energy substance is polydimethylsiloxane; the functional additive material is methylvinylcyclopentasiloxane, and the methylvinylcyclopentasiloxane is replaced by one of tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and octamethylcyclotetrasiloxane, or replaced by a mixture of methylvinylcyclopentasiloxane and tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and octamethylcyclotetrasiloxane, all of which can achieve the purpose of the present invention.
[0061] The preparation method of the bottom layer comprises the following steps: firstly, epoxy resin, polysiloxane and plasticizer are dissolved in an ethanol solution, magnetically stirred at a rotation speed of 800 rpm for 3.5 hours, and then ultrasonically dispersed for 55 minutes to obtain solution A; hydrophobic gas-phase nano-SiO2, toughening material and filler are mixed and dissolved in a second ethanol solution, magnetically stirred at a rotation speed of 800 rpm for 5 hours, and then ultrasonically dispersed for 35 minutes to obtain solution B; finally, the bottom layer solution is obtained by mixing solutions A, B, curing material and granular rough material and magnetically stirring at a rotation speed of 800 rpm for 1.5 hours.
[0062] The preparation method of the surface layer includes the following steps: firstly, dispersing hydrophobic gas-phase nano-SiO2 in anhydrous ethanol to obtain a gas-phase nano-silica suspension; then adding polydimethylsiloxane to the gas-phase nano-silica suspension, and magnetically stirring at 800 rpm for 3 hours; then adding functional additives, magnetically stirring at a speed of 800 rpm for 5 hours, and ultrasonically dispersing for 3 hours to obtain a surface layer solution.
[0063] In this example, the coating formed by compounding the bottom layer solution and the surface layer solution is simply brushed to prepare a double-layer multi-level super-hydrophobic coating on the substrate surface. After the bottom layer of the coating is coated on the substrate surface, it is placed at room temperature for 24 hours until the solvent evaporates and the coating solidifies. The surface layer and the bottom layer are compositely inlaid and coated, placed at 60°C for 50 minutes, and then cured for 12 hours at natural room temperature.
[0064] Embodiment 5
[0065] The coating consists of two parts, including a base coating and a surface coating, wherein the base raw materials include, by weight, 70 parts of solvent, 30 parts of high-strength adhesion material, 25 parts of toughening material, 3 parts of highly inert nanoparticles, 20 parts of film-forming material, 2 parts of plasticizer, 3 parts of filler, 12 parts of granular rough material, and 0.6 parts of curing material; the surface raw materials include, by weight, 25 parts of solvent, 1 part of highly inert nanoparticles, 1 part of low surface energy material, and 0.6 parts of functional additive material.
[0066] In this embodiment, the solvent is anhydrous ethanol, and the purpose of the present invention can be achieved by replacing anhydrous ethanol with one of acetone, toluene, and tetrahydrofuran, or by replacing it with a mixture of anhydrous ethanol and acetone, toluene, and tetrahydrofuran; the high-strength adhesive material is epoxy resin; the toughening material is polyester resin, and the purpose of the present invention can be achieved by replacing polyester resin with one of acrylic resin, polyurethane resin, and alicyclic polyamine, or by replacing it with a mixture of polyester resin and acrylic resin, polyurethane resin, and alicyclic polyamine; the highly inert nanoparticles are The LA-R649 in the hydrophobic gas-phase nano-SiO2 can be replaced by one of R202, R812, R812S, R972, R974, R106, LA-R669, TS-530, TS-610, and TS-720, or by a mixture of LA-R649 and R202, R812, R812S, R972, R974, R106, LA-R669, TS-530, TS-610, and TS-720, all of which can achieve the purpose of the present invention.
[0067] In this embodiment, the film-forming material is polysiloxane; the plasticizer is polymethyl methacrylate, and the purpose of the present invention can be achieved by replacing polymethyl methacrylate with one of phenolic resin and polypropylene, or by replacing it with a mixture of polymethyl methacrylate, phenolic resin and polypropylene; the filler is quartz powder, and the purpose of the present invention can be achieved by replacing quartz powder with one of talcum powder, aluminum powder or titanium dioxide, or by replacing it with a mixture of quartz powder and talcum powder, aluminum powder and titanium dioxide; the granular rough material is quartz sand, and the purpose of the present invention can be achieved by replacing quartz sand with one of river sand and machine-made sand, or by replacing it with a mixture of quartz sand and river sand or machine-made sand; the curing material is a straight-chain aliphatic polyamine, and the purpose of the present invention can be achieved by replacing the straight-chain aliphatic polyamine with one of polyamide and polythiol, or by replacing it with a mixture of straight-chain aliphatic polyamine, polyamide and polythiol.
[0068] In this embodiment, the low surface energy substance is polydimethylsiloxane; the functional additive material is octamethylcyclotetrasiloxane, and the purpose of the present invention can be achieved by replacing octamethylcyclotetrasiloxane with one of tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane, or replacing it with a mixture of octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane, and methylvinylcyclopentasiloxane.
[0069] The preparation method of the bottom layer comprises the following steps: firstly, epoxy resin, polysiloxane and plasticizer are dissolved in an ethanol solution, magnetically stirred at a rotation speed of 1500 rpm for 4.5 hours, and then ultrasonically dispersed for 55 minutes to obtain solution A; hydrophobic gas-phase nano-SiO2, toughening material and filler are mixed and dissolved in a second ethanol solution, magnetically stirred at a rotation speed of 1500 rpm for 3 hours, and then ultrasonically dispersed for 55 minutes to obtain solution B; finally, the bottom layer solution is obtained by mixing solutions A, B, curing material and granular rough material and magnetically stirring at a rotation speed of 1500 rpm for 1.8 hours.
[0070] The preparation method of the surface layer includes the following steps: firstly, dispersing hydrophobic gas-phase nano-SiO2 in anhydrous ethanol to obtain a gas-phase nano-silica suspension; then adding polydimethylsiloxane to the gas-phase nano-silica suspension, and magnetically stirring at 1500rpm for 3.3h; then adding functional additives, magnetically stirring at a speed of 1500rpm, and ultrasonically dispersing for 3 hours to obtain a surface layer solution.
[0071] In this example, the coating after the bottom layer solution and the surface layer solution are compounded is prepared by a simple brushing method to realize the preparation of a double-layer multi-level super hydrophobic coating on the substrate surface. After the coating bottom layer is coated on the substrate surface, it is placed at room temperature for 36 hours until the solvent evaporates and the coating solidifies. The surface layer and the bottom layer are compositely inlaid and coated, placed at 60°C and dried for 60 minutes, and then cured at natural room temperature for 24 hours.
[0072] The coating of the above-described embodiment is tested, and the static water contact angle of the coating reaches 163 ° ± 0.8 °, and the rolling angle is 3 ° ± 0.8 °. The coating still maintains super-hydrophobicity after 150 cycles of sandpaper friction under 300g pressure, and the contact angle decreases by only 6.1%. After 16h of water droplet penetration experiment and 12h of water flow impact experiment of the coating, the contact angle of the coating still remains at more than 153 ° and 151 °. After being soaked in acidic, alkaline and saline solutions for 8 hours respectively, the coating contact angle is still more than 150 °, and the rolling angle remains below 10 °, still maintaining super-hydrophobicity, showing good corrosion resistance.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A super-hydrophobic composite coating having a multi-layer self-similar anchoring structure, characterized in that: It comprises a super-hydrophobic bottom layer and a super-hydrophobic surface layer with a self-similar anchoring structure. The super-hydrophobic bottom layer and the super-hydrophobic surface layer interact with each other to form a micro-nano porous structure for bonding and anchoring the upper and lower layers. The coating surface has a multi-scale micro-nano composite structure. When the super-hydrophobic surface layer is worn, the super-hydrophobic bottom layer performs the hydrophobic function.
2. The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure according to claim 1, characterized in that: The raw materials of the super-hydrophobic bottom layer include solvents, high-strength adhesive materials, toughening materials, highly inert nanoparticles, film-forming materials, plasticizing materials, filler granular rough materials and curing materials; the raw materials of the super-hydrophobic surface layer include solvents, highly inert nanoparticles, low surface energy materials and silicone elastomers.
3. The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure according to claim 2, characterized in that: By weight, the raw materials of the super-hydrophobic base layer include 50-70 parts of solvent, 10-30 parts of high-strength adhesive material, 8-25 parts of toughening material, 1-3 parts of highly inert nanoparticles, 5-20 parts of film-forming material, 0.5-2 parts of plasticizer, 1-3 parts of filler, 8-12 parts of granular rough material, and 0.2-0.6 parts of curing material; the raw materials of the super-hydrophobic surface layer include 25-40 parts of solvent, 1-3 parts of highly inert nanoparticles, 1-3 parts of low surface energy material, and 0.6-1.5 parts of functional additive material.
4. The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure according to claim 3, characterized in that: The solvent is at least one of anhydrous ethanol, acetone, toluene, and tetrahydrofuran; the high-strength adhesive material is epoxy resin; the toughening material is at least one of polyester resin, acrylic resin, polyurethane resin, and alicyclic polyamine; the highly inert nanoparticles are at least one of R106, R202, R812, R812S, R972, R974, LA-R649, LA-R669, TS-530, TS-610, and TS-720 in hydrophobic gas-phase nano-SiO2.
5. The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure according to claim 4, characterized in that: The film-forming material is polysiloxane; the plasticizer is at least one of polymethyl methacrylate, phenolic resin, and polypropylene; the filler is at least one of quartz powder, talcum powder, aluminum powder, or titanium dioxide; the granular rough material is at least one of quartz sand, river sand, and machine-made sand; and the curing material is at least one of linear aliphatic polyamines, polyamides, and polythiol.
6. The super-hydrophobic composite coating with a multi-layer self-similar anchoring structure according to claim 2, characterized in that: The low surface energy substance is polydimethylsiloxane; the functional additive material is at least one of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, tetravinylcyclotetrasiloxane, methylvinylcyclotrisiloxane and methylvinylcyclopentasiloxane.
7. The method for preparing a super-hydrophobic composite coating having a multi-layer self-similar anchoring structure according to claim 1, characterized in that: The super-hydrophobic bottom layer solution is first applied to the surface of the substrate and solidified before being applied to the super-hydrophobic top layer solution.
8. The method for preparing a super-hydrophobic composite coating having a multi-layer self-similar anchoring structure according to claim 7, characterized in that: The preparation of the super hydrophobic bottom layer solution comprises the following steps: The high-strength adhesive material, the film-forming material and the plasticizing material are dissolved in a solvent, stirred and ultrasonically dispersed to obtain a solution A; the highly inert nanoparticles, the toughening material and the filler are mixed and dissolved in a solvent, stirred and ultrasonically dispersed to obtain a solution B; and the solution A, the solution B, the solidifying material and the granular rough material are mixed.
9. The method for preparing a super-hydrophobic composite coating having a multi-layer self-similar anchoring structure according to claim 7, characterized in that: The preparation method of the super-hydrophobic surface layer solution comprises the following steps: Highly inert nanoparticles are dispersed in anhydrous ethanol to obtain a gas-phase nano-silica suspension, and then a low surface energy substance is added and stirred, and finally a functional additive material is added and stirred and ultrasonically dispersed.
Citation Information
Patent Citations
Double-layer super-hydrophobic material and preparation method thereof
CN106119842A
Aluminum alloy super-hydrophobic corrosion-resistant coating and preparation method and application thereof
CN118162346A
Super-hydrophobic wear-resistant transparent coating and preparation method thereof
CN110078387A
Long-acting self-repairing super-hydrophobic ceramic coating as well as preparation method and application thereof
CN111303761A
Porous powder loaded with super-hydrophobic particles as well as preparation method and application of porous powder
CN113604095A